HOLOGRAPHIC TECHNOLOGIES OF EDUCATION AS A COMPONENT OF TRAINING OF FUTURE ENGINEERS IN THE CONDITIONS OF EDUCATIONAL AND INFORMATION ENVIRONMENT - Rakhmanov, Vitalii (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The article presents the results of training future engineers with the help of holographic technologies for lectures, practical and laboratory classes. When there is a global change (pandemic, war), education faces the risk that it will not be able to continue its usual processes and will have to move to instant managerial change. The aim of the article is to identify and outline the positive elements of holographic technologies that will help increase interactivity in the teaching and learning process. The task of the study is to find an alternative solution to attract the latest learning technologies in the training of future engineers. Experience shows that in this case, the educational and information environment is the best solution for classes. But the problem of learning is the interactivity of the student to improve the motivation of future professionals with the help of new technologies. At the Technical University, we propose to introduce innovative teaching and learning methods, including games, simulations and holograms. Meanwhile, training is not only the transfer of knowledge, but also an active, constructive and cognitive process through which the future engineer manages internal resources for the formation of key professional competencies. Research methods are to study and generalize domestic and foreign experience to substantiate the conceptual provisions of holographic learning technologies, structural and scientific analysis, as well as monitoring the learning process. Results. To improve the training of future engineers in an educational information environment, holographic technologies can be useful and become another resource that can change the way you create and conduct classes. To obtain this result, it is necessary to study the feasibility of holographic technologies in accordance with the training in the educational and information environment. The article reveals the essence of the considered holographic technologies, describes the advantages and features of their implementation in the educational process of the Technical University. This helps students to intensify cognitive activities and stimulate them to self-education. In the course of elaboration of a number of research ideas, various scientific approaches to the interpretation of the term "holographic technologies" are proposed. Conclusion. According to existing concepts, holographic technologies can be considered as a result of the creative process and as a process of innovation. Peculiarities, prospects of introduction of holographic technologies into the educational process of the technical university are determined, which require further detailed analysis and study in complex interaction with information systems.